If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14u + 10u + -1(-14) = 6 Multiply -1 * -14 -14u + 10u + 14 = 6 Reorder the terms: 14 + -14u + 10u = 6 Combine like terms: -14u + 10u = -4u 14 + -4u = 6 Solving 14 + -4u = 6 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -4u = 6 + -14 Combine like terms: 14 + -14 = 0 0 + -4u = 6 + -14 -4u = 6 + -14 Combine like terms: 6 + -14 = -8 -4u = -8 Divide each side by '-4'. u = 2 Simplifying u = 2
| 32-9=23 | | 0.5(18+12)=15 | | sin=3/4x-3=27 | | (5)(2b)-(5)(17)= | | f(x)=6x^4-5x^3-12x^2+5x+6 | | x+5x+4+x+2x-3x+6= | | 1x/2=3=6 | | 3/4x-3=27 | | 19.00+5.50x=11.00+6.75x | | 1/2x=3=6 | | 23x=-21 | | 2/5t=12/35 | | -4u-(-14)=6 | | m+14=8+2m | | 2x-5-8x=17 | | x-0.6=9.4 | | 9+(-9x)=-7 | | 5x+1=-5+10 | | 7K+2m=kr+4m+3fork | | 32x+-7=57 | | 12x-51=51+12x | | -10x-11=23-8x | | -3/8b=-3/4 | | 12x+3=69 | | -3/4b=-3/4 | | Ms+mw=r | | 32x-7=52 | | w+i+w+i= | | -6+5+15-1=0 | | X(2)-X-2=0 | | 4(2y-6)+3=6 | | 19=13+6(x-12) |